Risk Factors for Lymphedema after Thigh Sarcoma Resection and Reconstruction. Issue 7 (July 2020) - Wu, Peter; Elswick, Sarah M.; Arkhavan, Arya; Molinar, Vanessa E.; Mohan, Anita T.; Curiel, Daniel; Sim, Frank H.; Martinez-Jorge, Jorys; Saint-Cyr, Michel
Abstract : Background: Secondary lymphedema can be a lifelong and debilitating consequence of lower extremity oncologic resection and reconstruction. The goal of this study was to identify risk factors for the development of lymphedema in patients treated for thigh sarcoma. Methods: A retrospective review analyzed all patients who underwent thigh sarcoma resection and reconstruction by a plastic surgeon at the Mayo Clinic between 1997 and 2014. Patient demographics, tumor characteristics, surgical management, adjunctive therapies, and complications of patients who did and did not develop postoperative lymphedema were compared. Results: A total of 148 patients were identified. Twelve percent of patients developed lymphedema postoperatively during an average follow-up of 26 months. Risk factors for the development of lymphedema included defect location in the medial thigh ( P = 0.04), arterial resection ( P = 0.001), arterial reconstruction ( P = 0.027), and a history of cardiac disease ( P = 0.03). Twenty-two percent of patients who developed lymphedema also experienced wound dehiscence compared with 4.6% of patients without lymphedema ( P = 0.02). There were no differences in age, body mass index, smoking, history of deep venous thrombosis or venous stasis, wound dimensions, or type of reconstruction performed in patients with and without lymphedema. Conclusions: Lymphedema is common following major oncologic resection. Preexisting cardiac disease, tumor location in the medial thigh, and arterial resection and reconstruction were associated with a higher risk of postoperative lymphedema. Noninfectious wound dehiscence may be secondary to lymphedema or represent an early indicator of patients who will ultimately develop lymphedema.